Mucinous hidradenoma in a child—A case report and review of the literature. (11th May 2017) - Ahmed, Aadil; Kim, Wendy; Speiser, Jodi
Abstract : Hidradenomas are benign tumors of the sweat glands that are rarely reported in childhood. The presence of mucinous change in hidradenomas, which consists of variable numbers of mucin‐rich goblet cells, is occasionally observed in some adult clinical practices. However, it has not been previously reported in the pediatric population. Herein, we present a unique case of a mucinous hidradenoma presenting on the thigh of a 3‐year‐old boy. The clinical presentation and histological features of the case, along with a literature review of published case reports of pediatric hidradenomas are described. We present this case in order to highlight this variant of hidradenoma and to reinforce its inclusion in the differential diagnosis of neoplasms/conditions of childhood with mucinous differentiation.